Localization Methods of Weighted Centroid of dBZ on Weather-Radar Echo Maps in Vector Format - Xue-tao Yu; Xiao-ping Rui; Feng Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Fast generation of weather-radar echo maps in vector format and accurate localization of weighted centroid of dBZ (dBZ stands for decibels of reflectivity of a radar signal reflected off a remote object) are the basis of studying the characteristic tracking algorithms which are based on the vector echoes. The authors principally studied the approach to generating the vector echo map, and discussed the localization methods of weighted centroid of dBZ on vector echo maps. First, based on the traditional calculation method on raster echo data, some new localization methods of weighted centroid of dBZ on vector echo data were proposed by considering the weights of features’ area and distance from their location to radar center. Second, taking the base reflectivity products of CINRAD/SA weather radar in Meizhou city of China as data sources, they illustrated the storage structure of this type of echo data and studied the drawing mode of changing this type of data into vector format files under the polar coordinate system in detail. Third, using the same vector echo maps created by the above method, the weighted centroid of the same area was calculated by the above localization methods. In the end, Compared with the calculated value of the same area by traditional method which is based on raster echo maps, the three new calculated results and the sources of error were analyzed in detail and two conclusions were drawn: the echo’s precision in vector format is much higher than that in raster format and it is more accurate to take the features’ area and distance to radar center as weights during the calculation of weighted centroid of dBZ on echo maps in vector format. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2071